ANALISIS KESULITAN BELAJAR SISWA PADA MATERI HIMPUNAN - Sinta Ratnasari; Wahyu Setiawan (Journal on Education, 2019)
The purpose of this study was to describe the analysis of student learning difficulties in Grade VII students of SMP Mutiara 1 Bandung and examine students' mistakes in working on test questions regarding set material. This research method uses the description method. The study was conducted with the subject of the research were 29 students in class VII of Mutiara 1 Middle School Bandung. The test questions given are in the form of 5 description questions. The results of this study indicate that the seventh grade students of Mutiara 1 Bandung Junior High School already understood the concept of set, but students still did not master the pre-set material set, namely material of various numbers.